Meta‐analysis of randomized clinical trials of early versus delayed cholecystectomy for mild gallstone pancreatitis. Issue 11 (3rd July 2019) - Moody, N.; Adiamah, A.; Yanni, F.; Gomez, D.
Abstract : Background: Gallstones account for 30–50 per cent of all presentations of acute pancreatitis. While the management of acute pancreatitis is usually supportive, definitive treatment of gallstone pancreatitis is cholecystectomy. Guidelines from the British Society of Gastroenterology suggest definitive treatment on index admission or within 2 weeks of discharge, whereas joint recommendations from the International Association of Pancreatology and the American Pancreatic Association recommend definitive treatment on index admission. Evidence suggests that uptake of these guidelines is low. Methods: Embase, MEDLINE and Cochrane databases were searched for RCTs investigating early versus delayed cholecystectomy in patients with a confirmed diagnosis of mild gallstone pancreatitis. The pooled synthesis was undertaken using a random‐effects meta‐analysis of the primary outcome of recurrent biliary complications causing hospital readmission. Secondary outcomes included intraoperative and postoperative complications, and total length of hospital stay (LOS). All analyses were performed using RevMan5 software. Results: Five RCTs were identified, which included 629 patients (318 in the early cholecystectomy (EC) group and 311 in the delayed cholecystectomy (DC) group). Recurrent biliary events that required readmission were reduced in patients undergoing EC compared with the number in patients having DC (odds ratio (OR) 0·17, 95 per cent c.i. 0·09 to 0·33). There was no difference in the rate of intraoperative (OR 0·58, 0·17 to 1·92) or postoperative (OR 0·78, 0·38 to 1·62) complications. Conclusion: EC following mild gallstone pancreatitis does not increase the risk of intraoperative or postoperative complications, but reduces the readmission rate for recurrent biliary complications. Abstract : This meta‐analysis of RCTs evaluating early and late cholecystectomy in mild gallstone pancreatitis demonstrated that index admission cholecystectomy is safe and effective. It reduces the risk of recurrent biliary events and hospital readmissions with no increase in intraoperative or postoperative complications. Better early than late Abstract : Antecedentes: Los cálculos biliares son el factor etiológico en el 30‐50% de todas las formas de pancreatitis aguda. Si bien el tratamiento de la pancreatitis aguda suele ser de soporte, el tratamiento definitivo de la pancreatitis por litiasis biliar es la colecistectomía. La guía de la British Society of Gastroenterology sugiere efectuar el tratamiento definitivo en el mismo ingreso o dentro de las 2 semanas posteriores al alta, mientras que la International Association of Pancreatology y la American Pancreatic Association recomiendan de forma conjunta el tratamiento definitivo en el mismo ingreso. Los datos disponibles sugieren que el seguimiento de estas guías es bajo. Métodos: Se realizó una búsqueda en las bases de datos EMBASE, MEDLINE y Cochrane. de los ensayos clínicos aleatorizados y controlados ( randomized clinical trials, RCTs) que analizaron la colecistectomía precoz frente a la tardía en pacientes con una pancreatitis leve por litiasis biliar. Se efectuó un metaanálisis de efectos aleatorios en el que la variable principal era la recidiva de complicaciones biliares que motivasen el reingreso hospitalario. Como variables secundarias se analizaron las complicaciones intraoperatorias y postoperatorias. Así como la duración de la estancia hospitalaria ( length of stay, LOS). Los análisis se realizaron utilizando el programa RevMan5. Resultados: Se incluyeron 5 RCTs con 629 pacientes (grupo de colecistectomía temprana ( early cholecystectomy, EC), n = 318; grupo de colecistectomía tardía ( delayed cholecystectomy, DC); n = 311). La recidiva de la enfermedad biliar que requiriese reingreso hospitalario fue menor en los pacientes sometidos a EC en comparación con DC, (cociente de oportunidades, odds ratio, OR) 0, 17 (i.c. del 95% 0, 09‐0, 33). No hubo diferencias en la tasa de complicaciones intraoperatorias, OR 0, 58 (i.c. del 95% 0, 17‐1, 92) o postoperatorias, OR 0, 78 (i.c. del 95% 0, 38‐1, 62). Conclusión: La EC después de una pancreatitis leve por litiasis biliar no aumenta el riesgo de complicaciones intraoperatorias o postoperatorias, pero reduce la tasa de reingreso por la recidiva de complicaciones biliares.